Bones on fire: illuminating osteomyelitis through the radiant lens of 18F-FDG PET/CT - Yang, Mei; Tan, Quanhui; Tang, Zhenghao (Frontiers in Immunology, 2024)
Osteomyelitis is an inflammatory process that is caused by an infecting microorganism and leads to progressive bone destruction and loss. Osteomyelitis can occur at any age and can involve any bone. The infection can be limited to a single portion of the bone or can involve several regions, such as marrow, cortex, periosteum, and the surrounding soft tissue [1] .Early and accurate diagnosis plays a crucial role in reducing unnecessary treatment measures, improving the patient's prognosis, and minimizing time and financial costs. In recent years, the use of functional metabolic imaging has become increasingly widespread. Among them, 18 F-FDG PET/CT has emerged as a cutting-edge imaging modality that combines anatomical and functional metabolic information. It has seen rapid development in the field of infectious diseases. 18 F-FDG PET/CT has been demonstrated to yield acceptable diagnostic accuracy in a number of infectious and inflammatory diseases [2] . This review aims to provide information about the 18 F-FDGPET/CT in the use of chronic osteomyelitis ,osteomyelitis secondary to a contiguous focus of infection and osteomyelitis associated with peripheral vascular diease.